The Influence of Trust, Service Quality, Product Quality and Promotion in Shaping Repurchase Intention in Xl Axiata Providers - Hamdan, Hamdan; Nurul Rizka (Dinasti Research, 2021)
Communication is a human need that is quite important in everyday life. In this era of globalization, there have been many prepaid card products that are increasingly diverse, one of which is XL Axiata which is the first private cellular company in Indonesia. The purpose of this study was to determine Trust, Service Quality, Product Quality and Promotion in Forming Repurchase Intention in XL Axiata Provider Users. The subjects of this research are people who use the XL Axiata Provider in Jakarta. The sample used in this study was 145 respondents. The sampling technique was carried out by purposive sampling method. By using a quantitative descriptive approach. Analysis of the data used is statistical analysis in the form of SEM-PLS. The results of this study indicate that trust has a positive and insignificant effect on repurchase intention, service quality has a positive and insignificant effect on repurchase intention, product quality has a significant positive effect on repurchase intention and promotion has insignificant positive effect on repurchase intention.